Open book - Simpson, Jessica, 1980-; O'Leary, Kevin Carr (New York, NY : Dey St., an imprint of William Morrow, 2020)
Jessica reveals for the first time her inner monologue and most intimate struggles. Guided by the journals she's kept since age fifteen, and brimming with her unique humor and down-to-earth humanity, Open Book is as inspiring as it is entertaining.
Prologue -- A lesson in survival -- Singing my life -- Saved by failure -- Cheerleader blues -- Against all discouragement -- Taking flight -- Romeo and Juliet -- Eyeshadow abs -- Warning : contents under pressure -- Flight suits and wedding gowns -- Into the fishbowl -- Success has made a failure of our home -- The gilded cage -- I'll fly away -- Going off-script -- Playing dress-up -- Desire and possession -- They let you dream just to watch 'em shatter -- Return of the southern girl -- Death by mom jeans -- True beauty -- Love comes to my door -- Since I've been loving you -- Let's go dancing in the light -- Ever after -- I once was lost -- But now I see -- Birdie Mae.
Keywords: Simpson, Jessica, -- 1980-; Singers -- United States -- Biography; Actors -- United States -- Biography; Autobiographies